ANALISIS PENGARUH KUALIATAS PELAYANAN, PROMOSI DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELI SEPEDA MOTOR HONDA DI PANGKALPINANG (STUDI KASUS KONSUMEN PT. NUSANTARA SURYA SAKTI) - Waruwu, Mirani; Panjaitan, Fery; Tigor, Ryan Hasianda (Jurnal Progresif Manajemen Bisnis, 2023)
This research was entitled: “Analisis Pengaruh Kualitas Pelayanan, Promosi dan Desain Produk Terhadap Keputusan Pembeli Speda Motor Honda di Pangkalpinang”. This research is a descriptive quantitative research with a total sample of 100 respondents. This study has three independent variables, namely service quality, Promotion and Product Design and one dependent variable, namely Buyer Decision. Testing the instrument using the validity test and reliability test. The data analysis method used in this study is multiple linear regression analysis using the t test, f test, and analysis of the coefficient of determination (R2) Simultaneously significant influence between service quality, promotion and product design on the buyer’s decision. with F-count (214,298) > Ftable 1,984.